Magnetic susceptibility logs of four MeBo200 cores from RV MARIA S. MERIAN cruise MSM111 - Tilo von Dobeneck; Michal Kucera; Johan C Faust (PANGAEA, 2025)
All sediment series recovered during the MERIAN cruise MSM 111 by the MeBo 200 coring system were subject to routine magnetic susceptibility logging on the closed, full-length core segments. The magnetic volume susceptibility (κ) of marine sediments is primarily determined by their ferrimagnetic mineral content; paramagnetic matrix components, such as clays, are of minor relevance. κ is a dimensionless quantity that may vary from an absolute minimum value of -15 exttimes10^(-6) for diamagnetic minerals (such as water, pure carbonate or silicate) to a maximum value of approximately 10 exttimes10^(-3) for sediments rich in ferrimagnetic titanomagnetite (here mainly magmatic-sourced, ice-rafted or current-transported materials). Data were acquired on board using the MARUM Multi-Sensor Core Logging System (MSCLS), which is equipped with a BARTINGTON M.S.2 commercial susceptibility meter featuring an 85 mm wide loop sensor. Due to the sensor geometry, its sensitivity extends over a core interval of approximately 5 cm (half-width). Therefore, sharp susceptibility changes appear smoothed in the κ log and thin layers are not well resolved. To permit end-of-segment corrections and assess the thermal drift of the susceptibility meter, each core segment was measured separately. During post-processing, the top and bottom ends of each core section were mirror-corrected. The systematic decline of the susceptibility signal between segment boundaries was recovered by summing the overlapping tail data, resulting in datasets with minimal loss. MeBo200 cores are collected by sequentially pushing core barrels — referred to here as sections 1P, 2P, ..., xP — from the progressing borehole into the underlying sediment. Each barrel has a stroke length and corresponding potential recovery of 350 cm. The recovered core sections are cut into segments up to 120 cm long (or shorter). To calculate the nominal depth below the seafloor, the depth of each section at a given data point is added to the depth of the section top below the seafloor. Excess water in the liners appears to have liquefied some of the sandier sections during the retrieval and tilting of the MeBo system. This drilling-induced resuspension and subsequent redeposition of the sediment has caused some graded bedding, as reflected by the saw-tooth-like susceptibility patterns — these are clearly coring artefacts. Some segments also exhibited rotary deformation, primarily affecting directional magnetic data (i.e. NRM and anisotropy), but not volume susceptibility.